Safety of antidepressants commonly used in 6–17-year-old children and adolescents: A disproportionality analysis from 2014–2023 on the basis of the FAERS database - Yan Zhou; Yun Lu; Yu Wu; Wenqiang Kong; Lu Zhou; Xirui Guo; Hua Wei; Hongju Wang; Fangqing Xie; Shihao Yan; Fang Yang; Chun Liu; et al. (PLoS ONE, 2025)
Background Depression is a common mental disorder in children and adolescents, and antidepressants are widely used for treatment. This study aimed to explore and analyze adverse events (AEs) associated with antidepressant use in this population, providing insights for safety assessment. Methods This study extracted AE reports from the US FDA Adverse Event Reporting System (FAERS) for children and adolescents aged 6–17 years from 2014–2023, with fluoxetine, escitalopram, and sertraline as the primary suspected drugs. The study used the International Dictionary of Medical Terminology (MedDRA) to encode and classify AEs, and employed the reporting odds ratio (ROR) and proportional reporting ratio (PRR) methods for data mining. Results The FAERS database included 9,845 AE reports involving fluoxetine, escitalopram, and sertraline among children and adolescents aged 6–17 years. After removing duplicates, the analysis yielded 1,604, 352, and 571 AEs for fluoxetine, escitalopram, and sertraline, respectively. The study population demonstrated a sex distribution with approximately twice as many female patients as male patients, with most patients aged 12–17 years. At the system organ class (SOC) level, the AEs predominantly involved psychiatric disorders and nervous system disorders. Within the psychiatric disorders category at the high level group term (HLGT) level, the most frequently reported AE signals across all three medications were suicidal and self-injurious behaviors (not elsewhere classified, hereinafter referred to as NEC) and anxiety disorders and symptoms; For nervous system disorders, the predominant AE signals were neurological disorders (NEC) and movement disorders (including parkinsonism). At the Preferred Term (PT) level, the three antidepressants demonstrated similar AEs, including various suicidal and self-injurious behaviors, intentional overdose, neurological disorders (including serotonin syndrome, extravertebral reactions, etc) and prolonged QT. The typical AEs of fluoxetine included decreased appetite, insomnia, and urinary retention. Escitalopram was associated with additional AEs of sexual dysfunction and toxic epidermal necrolysis, whereas sertraline demonstrated unique associations with headache and rhabdomyolysis. Conclusion This study may offer further evidence regarding AEs associated with commonly prescribed antidepressants in children and adolescents. Overall, the findings are mostly consistent with the AEs recorded in the packaging instructions and previous reports. However, the study also identified previously unreported AEs and highlighted variations in the AE profiles across different demographic groups. As the causal relationships between these medications and the observed AEs remain to be fully elucidated, additional research is warranted to confirm these findings.